Sound power and radiation efficiency of a circular plate - CZARNECKI, Stefan; ENGEL, Zbigniew; PANUSZKA, Ryszard (Archives of Acoustics, 1981)
This paper considers the problem of estimating the sound radiation by vibrating surfaces in the case of a circular plate clamped on the circumference. The aim of this paper is to verify the values of the equivalent surfaces of the plate, which were obtained theoretically, with the experimental values obtained in the free field and reverberant field conditions. The results obtained show that there is a good agreement of results for k_{mn}a < 5. For k_{mn}a > 5 an increase in the sound radiation of the plate can be observed, which results both from a complex character of the vibration of the plate and from the effect of the acoustic field on the vibration conditions of the plate.